1996
DOI: 10.1002/zaac.19966221022
|View full text |Cite
|
Sign up to set email alerts
|

Über grünes Bis‐(2‐Iminoisopropyl‐thiophenolato)‐nickel(II) und weitere, ähnliche NiII‐Komplexe

Abstract: Die Verbindungen [NiII(iitp)2] 1 (iitp = 2‐Iminoisopropyl‐thiophenolat), [Ni 2II(imptp)2] · 2 CH3OH 2, eine Zweikernverbindung mit einem NiNi‐Abstand von 276 pm und [PPh4][NiII(imptp)(SCN)] 3 (imptp = 2‐(2‐Iminopentan‐4‐on)‐thiophenolat) wurden durch Umsetzung von Nickel(II)‐acetat‐tetrahydrat mit 2‐Iminoisopropyl‐thiophenol bzw. 2‐(2‐Iminopentan‐4‐on)‐thiophenol in Methanol dargestellt und durch Einkristallstrukturanalyse und andere physikalische Methoden charakterisiert. Das Redoxverhalten der Verbindungen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…Similarly, in complexes of type B [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] the CdN bond length of the Schiff base part is short at 1.29 ( 0.02 Å and the N-C phenyl bond is found at 1.41 ( 0.02 Å which is slightly shorter than the N-C phenyl bond in complexes of type A. Interestingly, the S-C phenyl bond length at 1.76 ( 0.02 remains the same as in type Ait is a C-S single bond. The phenyl ring is again aromatic with, in principle, six equivalent C-C bonds.…”
mentioning
confidence: 99%
“…Similarly, in complexes of type B [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] the CdN bond length of the Schiff base part is short at 1.29 ( 0.02 Å and the N-C phenyl bond is found at 1.41 ( 0.02 Å which is slightly shorter than the N-C phenyl bond in complexes of type A. Interestingly, the S-C phenyl bond length at 1.76 ( 0.02 remains the same as in type Ait is a C-S single bond. The phenyl ring is again aromatic with, in principle, six equivalent C-C bonds.…”
mentioning
confidence: 99%
“…The synthesis of the complex is described by Peyronel & Giusti (1981). For other benzothiazole derivatives, see: Duff et al (1969); Alyea & Malek (1985); Dey et al (1995); Mueller et al (1996).…”
Section: Related Literaturementioning
confidence: 99%
“…Benzothiazole derivatives and their complexes (Duff et al, 1969;Peyronel & Giusti, 1981;Alyea & Malek, 1985;Dey et al, 1995;Mueller et al, 1996) have been reported but the structure of the title compound has not been reported previously. The benzothiazoline derivatives were formed through the cyclocondensation of 2,4-pentanedione with 2aminobenzenethiol by refluxing in EtOH or DMSO (Alyea & Malek, 1985;Dey et al, 1995).…”
Section: S1 Commentmentioning
confidence: 99%
“…Der Faltungswinkel innerhalb des Chelatsechsrings ist deutlich größer (Diederwinkel: 29,4°). Damit wird eine mit dem anionischen Komplexmolekül Ni(LLL)(SCN)~ identische Konformation festge stellt [3]. Ein Vergleich der Bindungslängen des Li gandengerüstes bestätigt, daß die Struktur dieses Molekülteils von der Natur des einzähnigen Ligan den (PPh3 oder SCN~) unabhängig ist und daß die Enol-Form vorliegt.…”
Section: Molekülstruktur Von C24h20n4s2 (4)unclassified